Hubungan Islam Dan Negara Kajian Terhadap Pemikiran Abdurrahman Wahid Dan Amien Rais - Riani, Shofia; Dewi; Mutiara; Delviani; Firly (Tabayyun : Journal Of Islamic Studies, 2024)
The thoughts of Abdurrahman Wahid and Amien Rais, two influential figures in Indonesian political and religious history. Abdurrahman Wahid, known as Gus Dur, advocates inclusive and pluralist views, supporting a secular state that is neutral towards religion and promoting religious freedom and tolerance in a diverse society. On the other hand, Amien Rais supports the integration of Islamic values ​​in government systems and public policies to achieve social justice and morality. This study explores the differences in approaches of the two figures in interpreting the role of Islam in state governance and its impact on democracy and social harmony in Indonesia. Through this comparative analysis, this research aims to provide a deeper understanding of the dynamics of the relationship between Islam and the state in the Indonesian context, as well as its